2005
DOI: 10.1091/mbc.e05-01-0020
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol-4-Kinase Type II α Is a Component of Adaptor Protein-3-derived Vesicles

Abstract: A membrane fraction enriched in vesicles containing the adaptor protein (AP) -3 cargo zinc transporter 3 was generated from PC12 cells and was used to identify new components of these organelles by mass spectrometry. Proteins prominently represented in the fraction included AP-3 subunits, synaptic vesicle proteins, and lysosomal proteins known to be sorted in an AP-3-dependent way or to interact genetically with AP-3. A protein enriched in this fraction was phosphatidylinositol-4-kinase type II␣ (PI4KII␣). Bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
137
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(161 citation statements)
references
References 68 publications
23
137
1
Order By: Relevance
“…We estimate from such data that APP and Mint3 are increased in specific activity Ͼ10-fold over cell homogenate. Although this number may seem low in comparison with a standard protein purification, it is consistent with published procedures for the purification of synaptic (15-18-fold) (Huttner et al, 1983;Floor et al, 1988) or AP-3 (ϳ16-fold; Craige et al, 2005;Salazar et al, 2005) coated vesicles. The fold purification of vesicles was estimated from that of Mint3, which in turn was determined by comparison of immunoreactivity in V6 to serial dilutions of a bacterially expressed recombinant Mint3 standard.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…We estimate from such data that APP and Mint3 are increased in specific activity Ͼ10-fold over cell homogenate. Although this number may seem low in comparison with a standard protein purification, it is consistent with published procedures for the purification of synaptic (15-18-fold) (Huttner et al, 1983;Floor et al, 1988) or AP-3 (ϳ16-fold; Craige et al, 2005;Salazar et al, 2005) coated vesicles. The fold purification of vesicles was estimated from that of Mint3, which in turn was determined by comparison of immunoreactivity in V6 to serial dilutions of a bacterially expressed recombinant Mint3 standard.…”
supporting
confidence: 87%
“…Magnetic beads (Dynal Biotech, Oslo, Norway), coated with either anti-mouse (M480) or anti-rabbit (M280) immunoglobulin (IgG, were incubated with either mouse monoclonal antibodies to Mint3 or rabbit polyclonal antibody to APP, respectively in PBS/5% bovine serum albumin (BSA) for 2 h at room temperature, according to the Salazar et al (2005). Controls included substitution of either mouse monoclonal or rabbit polyclonal c-myc antibodies.…”
Section: Immunoisolation Of Vesicles and Immunogold Labelingmentioning
confidence: 99%
See 2 more Smart Citations
“…At2g40850 encodes a type II PtdIns 4-kinase, which has been previously named PI4Kg1 (Mueller-Roeber and Pical, 2002). While the function of type II PtdIns 4-kinases in plants is unknown, it has been suggested that in animals, they are involved in the regulation of intracellular trafficking (Wang et al, 2003;Salazar et al, 2005). Thus, the mutant phenotype observed for the At2g40850 insertion line might be caused by a malfunction of this essential cellular process.…”
Section: Identification Of Novel Regulators Of Microsporogenesismentioning
confidence: 99%